Battlements in the Military Architecture and in the Symbolism of the Ancient Near East - Porada, Edith (1967)
= Fs Wittkower, Part I; Part I deals with the archaeological evidence; Part II studies “Akkadian Terms Possibly Associated with Battlements (gabadibbû; samītu; pašqu; naburru; kilīlu; with the assistance of A. L. Oppenheim, E. Reiner and Joyce Bartels).